กรอบแนวคิดการติดต่อสื่อสารระหว่างบ้านและโรงเรียน - เที่ยงธรรมเจริญ ทศา; ชูประวัติ เพ็ญวรา (An Online Journal of Education, 2018)
This study was documentary research. The purpose of this research were 1) to study the conceptual framework of Communication objectives 2) to study the conceptual framework of Communication channels between parents and school 3) to study the conceptual framework of Information communicated between parents and school. A documentary synthesis method was used. The research instrument was records. Data were analyzed by content analysis. The finding were as follows: 1. The conceptual framework of Communication objectives composed of 1.1 to inform, 1.2 to educate, 1.3 to persuade, 1.4 to entertain. 2. The conceptual framework of Information communicated between parents and school composed of 2.1 School policy, 2.2 Curriculum and learning approaches, 2.3 Students development, 2.4 Activities and projects, 2.5 News, 2.6 Problem and emergency. 3. The conceptual framework of Communication channels between parents and school composed of 3.1 Written media, 3.2 Telephone, 2.3 Meeting, 2.4 New media